Designing Synchronous and Asynchronous Activities for Interactive Learning - Handoko Handoko; Ayumi Ayumi (JURNAL ARBITRER, 2022)
This study aims to develop a model of interactive learning media by focusing on online activities with synchronous and asynchronous models to improve the quality of English learning. The study provides some discussion about preparing an interactive online learning by deploying various types of activities which group into synchronous and asynchronous activities. The method used in the research is research and development method which follows ADDIE model. The data collected from English skill class which include Elementary Reading and Writing and Elementary Listening and Speaking. The result of the study shows effective model for developing interactive medias for teaching English skill. It is very important to design learning activities aligned with the learning outcomes and learning objectives. To create an effective online learning environment, teachers should consider about the interactivity of the learning activities and the mode of content delivery. Both synchronous and asynchronous activities have benefits and drawback. Hence to get a maximum benefit of online learning, teachers need to combine synchronous and asynchronous activities and design which activities should be delivered in each mode.